Particle electrode for enhancing electro-catalytic degradation of pollutants in industrial wastewater as well as preparation method and application of particle electrode
By loading Fe-g-C3N4 on biochar and reloading TiO2, TiO2 is formed to form a TiO2/Fe-g-C3N4/BC particle electrode. Combined with photocatalysis and electrocatalysis technology, the short life and catalytic ability of electrode materials in electrocatalysis technology are solved. Limited problems have significantly improved the degradation effect of pollutants and electrode stability in industrial wastewater.
Patent Information
- Application Number
- CN202411744821.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-12-02
AI Technical Summary
When degrading pollutants in industrial wastewater, existing electrocatalytic technologies have problems such as short life, limited catalytic capacity and high cost of electrode materials, especially low efficiency for wastewater treatment with high salt or high organic content.
Using TiO2/Fe-g-C3N4/BC particle electrode, a three-dimensional electrocatalytic system is formed by loading Fe-g-C3N4 on biochar and TiO2 on it, and combining photocatalytic and electrocatalytic technologies to improve pollutant degradation Effect.
It significantly improves the pollutant degradation effect and electrode stability of electrocatalytic oxidation technology, improves the removal rate of typical pollutants in industrial wastewater, and reduces treatment costs.
Smart Images

Figure CN119219135A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemistry and sewage treatment, and specifically relates to a particle electrode for enhancing the electrocatalytic degradation of pollutants in industrial wastewater, and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Although great progress has been made in the field of wastewater treatment with the continuous development of science and technology, the overall volume of industrial water consumption is still large, and the industry still faces a large demand for industrial wastewater treatment. Problems such as substandard industrial wastewater discharge still exist widely. Industrial wastewater has complex components, unstable water quality and water volume, and high concentrations of chemical oxygen demand (COD). Since industrial wastewater often contains a variety of toxic substances, most of which have "three-cause" toxicity, wanton discharge will cause great harm to the water ecological environment and threaten human health and safety. Therefore, it is becoming more and more urgent to develop a new and efficient method to treat industrial wastewater, which has become a hot topic of concern.
[0004] At present, traditional biological treatment, Fenton oxidation, membrane separation and other methods are all applicable to industrial wastewater treatment, but they are not targeted, have low efficiency or high energy consumption, produce more by-products, or react with non-target oxides after oxidation to produce many unknown or more toxic substances. Among them, the emerging electrocatalytic oxidation technology has the advantages of high pollutant degradation efficiency, no secondary pollution, and simple operation. It provides a new way for industrial wastewater treatment, especially for difficult-to-degrade wastewater with high salt or high organic content. It has great potential.
[0005] Electrocatalytic oxidation is to apply a certain voltage to wastewater, so that pollutants undergo oxidation reaction under the action of the electric field, degrade into small molecules that are easily degradable pollutants or directly mineralize into water and carbon dioxide, and then remove them from the wastewater. Electrocatalytic oxidation technology provides a promising method for the field of industrial wastewater treatment, with advantages such as environmental compatibility, small footprint, and rapid reaction; compared with biochemical treatment processes, electrocatalytic oxidation technology has a fast reaction rate, can degrade organic matter that is difficult to biodegrade, and improve the biodegradability of wastewater; compared with advanced oxidation technologies such as photocatalysis and Fenton, electrocatalytic oxidation technology has the advantages of mild reaction conditions and low operating conditions.
[0006] Commonly used electrocatalytic oxidation technologies generally use two-dimensional electrode systems, but in practical applications, there are defects such as short life and high price of electrode materials, limited electrode reaction area, low current efficiency and degradation efficiency. Therefore, researchers have proposed a three-dimensional electrocatalytic reaction system to improve the efficiency of electrochemical reactions and reduce the cost of pollutant removal. A three-dimensional electrocatalytic system is a two-dimensional electrode system in which powder or granular materials (i.e., particle electrodes, also known as third electrodes) are filled between electrodes. Under the action of the electric field, the particle electrodes become microelectrodes, which increases the electrode active area and the surface-to-body ratio of the reactor, enhances the mass transfer efficiency, and thus improves the degradation effect of pollutants. In addition, particle electrodes have a large specific surface area, which makes them easy to combine with the reaction medium, and can adsorb a large amount of pollutants, providing more reaction sites for the catalytic reaction, thereby improving the degradation efficiency. Particle electrodes can also improve the current distribution and effectiveness of electrochemical oxidation. Therefore, the performance of particle electrodes plays an extremely critical role in three-dimensional electrode systems, and people often focus on particle electrodes in three-dimensional electrocatalytic technology.
[0007] Commonly used particle electrodes include activated carbon, metal particles and nickel foam. Among them, activated carbon is widely used as a particle electrode due to its excellent electrode properties such as high adsorption, good conductivity, high chemical stability, etc. Although activated carbon particle electrodes have extremely strong adsorption capacity, their catalytic capacity is limited. After adsorbing pollutants, they cannot completely degrade them, clogging the micropores on the surface of activated carbon, causing the catalytic performance of activated carbon particle electrodes to gradually decrease, affecting the treatment effect of wastewater. Therefore, the preparation of particle electrodes with high catalytic activity has become a current research hotspot. In order to solve the above problems, how to improve the electrocatalytic oxidation performance of particle electrodes by loading metals and their oxides and composite oxide materials with high catalytic activity on the surface of activated carbon is an important research hotspot at present. Summary of the invention
[0008] In order to solve the problems existing in electrocatalysis in the degradation of refractory pollutants in industrial wastewater, the purpose of the present invention is to provide a particle electrode for enhanced electrocatalytic degradation of pollutants in industrial wastewater and its preparation method and application. The particle electrode for enhanced electrocatalytic degradation of pollutants in industrial wastewater provided by the present invention, the particle electrode is loaded with a photocatalytic material, which can not only improve the stability of the particle electrode, but also effectively combine photocatalysis and electrocatalysis, thereby improving the degradation effect.
[0009] In order to achieve the above object, the technical solution of the present invention is: In the first aspect, the present invention provides a particle electrode for enhanced electrocatalytic degradation of pollutants in industrial wastewater, wherein the particle electrode is a TiO2 / Fe-g-C3N4 / BC particle electrode, wherein BC is porous biochar, Fe-g-C3N4 is loaded on BC, and TiO2 is loaded on Fe-g-C3N4 / BC.
[0010] The Fe-g-C3N4 is g-C3N4 doped with metal Fe.
[0011] In one or more embodiments, the mass of the iron source is 5-10% of the mass of g-C3N4, the mass of Fe-g-C3N4 is 5%-10% of the mass of BC, and the mass of TiO2 is 10%-15% of the mass of Fe-g-C3N4 / BC.
[0012] In a second aspect, the present invention provides the above-mentioned method for preparing a particle electrode for enhanced electrocatalytic degradation of pollutants in industrial wastewater, comprising the following steps: Preparation of biochar by pyrolysis of biomass raw materials; Preparation of Fe-g-C3N4 using g-C3N4 and iron source; Fe-g-C3N4 / BC was prepared using biochar and Fe-g-C3N4; TiO2 / Fe-g-C3N4 / BC particle electrode was prepared using Fe-g-C3N4 / BC and TiO2.
[0013] In one or more embodiments, the biomass raw material is wood or straw. Considering the concept of low cost and sustainable development, solid waste resource-straw is preferred. The straw includes reed straw, corn straw, wheat straw, etc.
[0014] In one or more embodiments, the biomass raw material is crushed and sieved. The crushing is to use a crusher to mechanically crush the biomass, and sieve to obtain 100-300 mesh for standby use, preferably 200 mesh.
[0015] In one or more embodiments, the biomass raw materials obtained by crushing and screening are dried or sprayed with water so that the moisture content of the biomass raw materials is maintained at 15% to 20%.
[0016] In one or more embodiments, the pyrolysis temperature is 400-600°C, the pyrolysis time is 2-6h, and the heating rate is 3-8°C / min. Preferably, the pyrolysis temperature is 500°C, and the pyrolysis time is maintained for 4h, and the heating rate of the tubular furnace is 5°C / min.
[0017] In one or more embodiments, biochar (BC) is pretreated by soaking in acid and alkali to remove its ash and modify it. The purpose of the modification is to increase the surface functional group content of biochar, improve its adsorption performance and enhance its chemical reaction activity. Specifically, it is soaked and shaken in an alkaline solution and an acid solution respectively. The alkaline solution is a 1-3 mol / L sodium hydroxide (NaOH) solution, and the acid solution is a 1-3 mol / L dilute hydrochloric acid (HCL) solution. The shaking conditions are a rotation speed of 100-300 r / min and an shaking time of 1-2 h.
[0018] After the soaking, the process also includes water washing to adjust the pH to neutral, ultrasonic cleaning, and drying. Specifically, it is washed with deionized water until the pH of the cleaning solution is neutral (pH=6.5-7.2), and finally ultrasonic cleaning is used. After the cleaning, it is dried at 80-110°C.
[0019] In one or more embodiments, the preparation process of Fe-g-C3N4 using g-C3N4 and an iron source is as follows: g-C3N4 and an iron source are dissolved in water, mixed and stirred, and then separated, washed, and dried to obtain Fe-g-C3N4.
[0020] Furthermore, the g-C3N4 is prepared by calcining and grinding melamine as a raw material. The calcination temperature is 400-600°C, the calcination time is 2-6h, the heating rate is 4-6°C / min, and after cooling to room temperature after calcination, it is taken out and fully ground with an agate mortar to obtain powdered g-C3N4 (black phase carbon nitride). A tubular furnace can be used for calcination in the process.
[0021] Furthermore, the iron source includes ferric nitrate nonahydrate (Fe(NO3)3∙9H2O) or ferric chloride hexahydrate.
[0022] The mass of the iron source is 5-10% of the mass of g-C3N4.
[0023] Furthermore, during the stirring, an alcohol solution of sodium borohydride with a concentration of 4-8 mg / mL is added. Specifically, after the g-C3N4 powder is dissolved in deionized water at 10-60°C, Fe(NO3)3∙9H2O is used as a loaded iron source for mechanical stirring for 20-40 minutes, and during the stirring process, 1-2 mL of an alcohol solution of sodium borohydride with a concentration of 4-8 mg / mL is added and stirring is continued for 20-40 minutes, centrifuged, and the precipitate is washed and dried to obtain Fe-g-C3N4.
[0024] The sodium borohydride added during the stirring process is used as a reducing agent to reduce iron ions to iron nanoparticles. Alcohol is used as a solvent to help the uniform dispersion of sodium borohydride and its full reaction with iron ions.
[0025] In one or more embodiments, the process of preparing Fe-g-C3N4 / BC using biochar and Fe-g-C3N4 is as follows: the pretreated biochar and Fe-g-C3N4 are dissolved in water, stirred, dried, and calcined to obtain Fe-g-C3N4 / BC.
[0026] Furthermore, the stirring time is 6-14h, the drying temperature is 100-110°C, the calcination temperature is 400-500°C, the calcination time is 2-4h, and the heating rate is 2-6°C / min.
[0027] The mass of Fe-g-C3N4 is 5%-10% of the mass of BC. If the loading is too large, the amount of BC will decrease, and the adsorption performance of BC will deteriorate; if the loading is too small, the amount of Fe-g-C3N4 will be small, and the photocatalytic performance of Fe-g-C3N4 will be poor.
[0028] Specifically: the pretreated biochar is mixed with water for 2-3 hours, and then the Fe-g-C3N4 is dissolved in the suspension and mechanically stirred for 6-14 hours to allow it to be fully adsorbed. After completion, it is dried at 80-110°C, and then calcined in a tubular furnace under a nitrogen atmosphere at 400-500°C for 2-4 hours, and the temperature is increased at a rate of 2-6°C / min. After cooling to room temperature, it is taken out to obtain Fe-g-C3N4 / BC.
[0029] In one or more embodiments, the preparation process of TiO2 / Fe-g-C3N4 / BC particle electrode using Fe-g-C3N4 / BC and TiO2 is: adding a binder and a dispersant to TiO2 powder to obtain a TiO2 mixture, and then mixing, drying, and calcining the Fe-g-C3N4 / BC and TiO2 mixture.
[0030] Furthermore, the preparation method of the TiO2 powder includes a sol-hydrothermal method, a sol-gel method, etc., preferably a sol-hydrothermal method, which can overcome the defects of the calcination process in the sol-gel method and utilize high temperature and high pressure conditions to enhance the dissolution effect of the formed gel.
[0031] Preferably, the preparation method of the TiO2 powder is to use tetrabutyl titanate as a raw material, and to obtain the powder by sol hydrothermal method, calcination and grinding. That is, first prepare the TiO2 sol, then perform hydrothermal reaction, and finally calcine and grind to obtain titanium dioxide (TiO2) powder.
[0032] Specifically, anhydrous ethanol and tetrabutyl titanate are fully stirred and mixed in a ratio of (2-3):1 to obtain solution A; anhydrous ethanol and water are mixed in a ratio of (3-4):1, and 0.1-2mL of HNO3 (70%) solution is added and stirred to obtain solution B; solution A is slowly added to solution B and mixed and stirred for 0.5-2h to obtain TiO2 sol. The TiO2 sol is subjected to a hydrothermal reaction at a hydrothermal temperature of 150-200℃ and a hydrothermal time of 4-6h. After the reaction is completed, the reaction solution is dried at 80-110℃, calcined in a nitrogen atmosphere for 1-3h, the calcination temperature is 400-600℃, the heating rate is 4-6℃ / min, and the calcination environment is an inert gas atmosphere to obtain TiO2 solid material, which is cooled to room temperature and ground into powder for use.
[0033] Furthermore, the adhesive is 10 wt% polytetrafluoroethylene or polyetherketone (PEEK).
[0034] The dispersant is anhydrous ethanol.
[0035] In the TiO2 mixture, the ratio of TiO2, binder and dispersant is 1:(1.5-3):(1.5-3), g / mL / mL.
[0036] In order to better load TiO2 on Fe-g-C3N4 / BC, a binder and a dispersant are first added to the TiO2 powder to obtain a TiO2 mixture. The specific preparation process is: the binder and the dispersant are mixed, then added dropwise to the TiO2 powder and heated and ultrasonicated to obtain a TiO2 mixture. The ultrasonication time is 1-2h.
[0037] Furthermore, in the preparation process of mixing, drying and calcining the Fe-g-C3N4 / BC and TiO2 mixture, the drying temperature is 80-110°C, the drying time is 0.5-2h, the calcination temperature is 300-500°C, the heating rate is 2-6°C / min, the calcination time is 4-5h, and the calcination environment is an inert gas atmosphere.
[0038] Among them, the mass of TiO2 is 10%-15% of the mass of Fe-g-C3N4 / BC.
[0039] In a third aspect, the present invention provides the use of the above-mentioned particle electrode for enhancing the electrocatalytic degradation of pollutants in industrial wastewater in enhancing the electrocatalytic degradation of pollutants in industrial wastewater.
[0040] The wastewater includes wastewater containing tetrahydrofuran (THF) and / or N,N-dimethylformamide (DMF), chemical wastewater, pharmaceutical wastewater, pesticide wastewater, etc.
[0041] In a fourth aspect, the present invention provides a method for enhancing electrocatalytic degradation of pollutants in industrial wastewater, comprising the following steps: (1) constructing a three-dimensional electrocatalytic oxidation system in an electrolytic cell, the system comprising an anode, a cathode, an electrolyte solution and a particle electrode suspended in the electrolyte solution; the particle electrode is a particle electrode for enhancing electrocatalytic degradation of pollutants in industrial wastewater prepared by the above method; (2) mixing industrial wastewater with the electrolyte solution; (3) applying voltage in the three-dimensional electrocatalytic oxidation system to electrocatalytically oxidize the industrial wastewater.
[0042] Specifically, the above-mentioned TiO2 / Fe-g-C3N4 / BC particles were used as particle electrodes for electrocatalytic degradation of pollutants, and two pairs of working electrodes were adopted. The working electrodes included two anodes and three cathodes. The cathodes were made of titanium plates, and the anodes were made of DSA electrodes (titanium-based oxide coated electrodes) or BDD electrodes (boron-doped diamond electrodes). The power supply was a DC regulated power supply.
[0043] Wherein, the DSA electrode is a DSA ruthenium-iridium electrode.
[0044] Furthermore, the dosage of TiO2 / Fe-g-C3N4 / BC particle electrode is 1-5g / L, preferably 1-2g / L.
[0045] Furthermore, the electrolyte solution is 10-30 mmol / L Na2SO4, preferably 15-25 mmol / L.
[0046] Furthermore, the distance between the electrodes is 1-3 cm.
[0047] Furthermore, the current density of the electrocatalytic oxidation system is 10-30 mA / cm 2 , preferably 15-25mA / cm 2 .
[0048] The beneficial effects of the present invention are: (1) The TiO2 / Fe-g-C3N4 / BC particle electrode material prepared by the present invention has a rich porous structure and has good electrocatalytic oxidation ability. The particle electrode is loaded with photocatalytic materials, which can not only improve the stability of the particle electrode, but also effectively combine photocatalysis and electrocatalysis, thereby improving the degradation effect of electrocatalytic oxidation technology on typical pollutants in industrial wastewater.
[0049] (2) A three-dimensional electrocatalytic oxidation system is formed by using TiO2 / Fe-g-C3N4 / BC particle electrodes. Compared with the two-dimensional electrocatalytic oxidation system, the degradation and removal effect of typical pollutants in industrial wastewater has been greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0051] Figure 1 The degradation effect diagram of tetrahydrofuran as the target pollutant in Example 1 of the present invention and Comparative Example 1 is shown; Figure 2 This is a diagram showing the degradation effect of N,N-dimethylformamide as the target pollutant in Example 3 of the present invention and Comparative Example 2; Figure 3 This is a diagram showing the degradation effect of wastewater from a chemical plant as the target pollutant in Example 4 and Comparative Example 3 of the present invention; Figure 4 This is a diagram showing the degradation effect of pharmaceutical wastewater from a pharmaceutical factory as the target pollutant in Example 5 and Comparative Example 4 of the present invention; Figure 5This is a diagram showing the degradation effects of wastewater from a pesticide factory as the target pollutant in Example 6 of the present invention and Comparative Example 5. DETAILED DESCRIPTION
[0052] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0053] Example 1 (1) Biochar preparation The reed straw was crushed with a crusher and passed through a 200-mesh sieve for later use. The moisture content of the straw was maintained at 15% to 20% by drying or spraying water. It was pyrolyzed and carbonized at 500°C for 4 hours in a nitrogen atmosphere in a tubular furnace, and the heating rate was 5°C / min. The biochar was recorded as BC. After sieving BC (150 mesh), the surface impurities were washed with deionized water, and then BC was first soaked in a 1mol / L sodium hydroxide (NaOH) solution and oscillated at room temperature (100r / min) for 1h. After the soaking, it was moved to a 1mol / L dilute hydrochloric acid (HCL) solution and oscillated (100r / min) for 1h. After the soaking, it was washed with deionized water until the pH of the washing solution was neutral (pH=6.5-7.2), and finally ultrasonically cleaned. After the cleaning, it was dried in an oven at 105°C.
[0054] (2) Preparation of g-C3N4 Melamine was used as raw material, calcined at 550°C for 4 hours with a heating rate of 5°C / min, and then fully ground with an agate mortar after cooling to room temperature to obtain a powdered g-C3N4 material.
[0055] (3) Preparation of Fe-g-C3N4 Take 4g of powdered g-C3N4 and stir it in 20mL of 50℃ deionized water for 10min, then add 0.3gFe(NO3)3∙9H2O and stir mechanically for 30min, then add 1mL of 6mg / mL sodium borohydride alcohol solution, continue stirring for 30min and centrifuge. The precipitate is washed with deionized water and anhydrous ethanol respectively, and dried in an oven. The obtained sample is recorded as Fe-g-C3N4.
[0056] (4) Preparation of Fe-g-C3N4 / BC Take 20g of pretreated BC and ultrasonically mix it with deionized water for 2h to make a suspension, then dissolve 2g of Fe-g-C3N4 in it and stir it mechanically for 12h to allow it to be fully adsorbed. After the end, move it to an oven and dry it at 105℃. After the end, calcine it in a tubular furnace under a nitrogen atmosphere at 450℃ for 4h, increase the temperature at a rate of 5℃ / min, and take it out after cooling to room temperature to obtain Fe-g-C3N4 / BC.
[0057] (5) Preparation of TiO2 Take 40mL of anhydrous ethanol and slowly add 20mL of tetrabutyl titanate under magnetic stirring, stir and mix thoroughly to obtain solution A; take 30mL of anhydrous ethanol, add 10mL of distilled water and 0.12mL of HNO3 (70%) and stir and mix thoroughly to obtain solution B. Slowly add solution A to solution B and stir for 1h. The obtained TiO2 sol is transferred to a hydrothermal reactor and heated at 180℃ for 5h. After the reaction, it is dried in an oven at 105℃. The dried material is then calcined in a tubular furnace at 450℃ for 2h to obtain TiO2 solid material.
[0058] (6) Preparation of TiO2 / Fe-g-C3N4 / BC Take 1.5g TiO2 powder, stir and mix 2mL 10% PTFE and 2mL anhydrous ethanol, add dropwise into it and heat and ultrasonic for 1h to obtain TiO2 mixture. Then stir it evenly with 10g Fe-g-C3N4 / BC and move it to an oven to dry at 105℃. After drying, calcine it in a tubular furnace under nitrogen atmosphere at 400℃ for 4h, with a heating rate of 5℃ / min, to obtain TiO2 / Fe-g-C3N4 / BC particle electrode.
[0059] Fe-g-C3N4 is g-C3N4 doped with metal Fe; Fe-g-C3N4 is uniformly loaded on the surface and pores of BC, and TiO2 is uniformly loaded on the surface or pores of Fe-g-C3N4 / BC.
[0060] In this embodiment, the constructed three-dimensional electrocatalytic oxidation system is used to remove the industrial organic solvent tetrahydrofuran (THF). The prepared TiO2 / Fe-g-C3N4 / BC particles are used as particle electrodes for electrocatalytic degradation of pollutants. Two pairs of working electrodes (two anodes and three cathodes) are used. The cathode is a titanium plate, and the anode is a DSA ruthenium iridium electrode. The power supply is a DC regulated power supply. They are assembled into a three-dimensional electrocatalytic oxidation system and an electrochemical catalytic oxidation test is carried out.
[0061] Tetrahydrofuran (THF) was used as the target pollutant, and the experimental water was prepared with a COD of 1500 mg / L. The electrolyte was 20 mmol / L Na2SO4, the dosage of the particle electrode TiO2 / Fe-g-C3N4 / BC was 1 g / L, the electrode spacing was 2 cm, and the current density of the electrocatalytic oxidation system was regulated to 20 mA / cm 2 .like Figure 1 As shown, the removal rate of tetrahydrofuran (THF) by the three-dimensional electrocatalytic oxidation system reached more than 85.23%; the above experiments proved that the TiO2 / Fe-g-C3N4 / BC particle electrode prepared by the present invention can achieve efficient degradation of pollutants.
[0062] Example 2 (1) Biochar preparation The reed straw was crushed with a crusher and passed through a 200-mesh sieve for later use. The moisture content of the straw was maintained at 15% to 20% by drying or spraying water. It was pyrolyzed and carbonized at 500°C for 4 hours in a nitrogen atmosphere in a tubular furnace, and the heating rate was 5°C / min. The biochar was recorded as BC. After sieving BC (150 mesh), the surface impurities were washed with deionized water, and then BC was first soaked in a 1mol / L sodium hydroxide (NaOH) solution and oscillated at room temperature (100r / min) for 1h. After the soaking, it was moved to a 1mol / L dilute hydrochloric acid (HCL) solution and oscillated (100r / min) for 1h. After the soaking, it was washed with deionized water until the pH of the washing solution was neutral (pH=6.5-7.2), and finally ultrasonically cleaned. After the cleaning, it was dried in an oven at 105°C.
[0063] (2) Preparation of g-C3N4 Melamine was used as raw material, calcined at 550°C for 4 hours with a heating rate of 5°C / min, and then fully ground with an agate mortar after cooling to room temperature to obtain a powdered g-C3N4 material.
[0064] (3) Preparation of Fe-g-C3N4 Take 4g of powdered g-C3N4 and stir it in 20mL of 50℃ deionized water for 10min, then add 0.3gFe(NO3)3∙9H2O and stir mechanically for 30min, then add 1mL of 6mg / mL sodium borohydride alcohol solution, continue stirring for 30min and centrifuge. The precipitate is washed with deionized water and anhydrous ethanol respectively, and dried in an oven. The obtained sample is recorded as Fe-g-C3N4.
[0065] (4) Preparation of Fe-g-C3N4 / BC Take 20g of pretreated BC and ultrasonically mix it with deionized water for 2h to make a suspension, then dissolve 2g of Fe-g-C3N4 in it and stir it mechanically for 12h to allow it to be fully adsorbed. After the end, move it to an oven and dry it at 105℃. After the end, calcine it in a tubular furnace under a nitrogen atmosphere at 450℃ for 4h, increase the temperature at a rate of 5℃ / min, and take it out after cooling to room temperature to obtain Fe-g-C3N4 / BC.
[0066] (5) Preparation of TiO2 Take 40mL of anhydrous ethanol and slowly add 20mL of tetrabutyl titanate under magnetic stirring, stir and mix thoroughly to obtain solution A; take 30mL of anhydrous ethanol, add 10mL of distilled water and 0.12mL of HNO3 (70%) and stir and mix thoroughly to obtain solution B. Slowly add solution A to solution B and stir for 1h. The obtained TiO2 sol is transferred to a hydrothermal reactor and heated at 180℃ for 5h. After the reaction, it is dried in an oven at 105℃. The dried material is then calcined in a tubular furnace at 450℃ for 2h to obtain TiO2 solid material.
[0067] (6) Preparation of TiO2 / Fe-g-C3N4 / BC Take 1g TiO2 powder, stir and mix 2mL 10% PTFE and 2mL anhydrous ethanol, add dropwise into it and heat and ultrasonic for 1h to obtain TiO2 mixture. Then stir it evenly with 10g Fe-g-C3N4 / BC and move it to an oven to dry at 105℃. After drying, calcine it in a tubular furnace under nitrogen atmosphere at 400℃ for 4h, with a heating rate of 5℃ / min, to obtain TiO2 / Fe-g-C3N4 / BC particle electrode.
[0068] In this embodiment, the constructed three-dimensional electrocatalytic oxidation system is used to remove the industrial organic solvent tetrahydrofuran (THF). The prepared TiO2 / Fe-g-C3N4 / BC particles are used as particle electrodes for electrocatalytic degradation of pollutants. Two pairs of working electrodes (two anodes and three cathodes) are used. The cathode is a titanium plate, and the anode is a DSA ruthenium iridium electrode. The power supply is a DC regulated power supply. They are assembled into a three-dimensional electrocatalytic oxidation system and an electrochemical catalytic oxidation test is carried out.
[0069] Tetrahydrofuran (THF) was used as the target pollutant, and the experimental water was prepared with a COD of 1500 mg / L. The electrolyte was 20 mmol / L Na2SO4, the dosage of the particle electrode TiO2 / Fe-g-C3N4 / BC was 1 g / L, the electrode spacing was 2 cm, and the current density of the electrocatalytic oxidation system was regulated to 20 mA / cm 2 .like Figure 1 As shown, the removal rate of tetrahydrofuran (THF) by the three-dimensional electrocatalytic oxidation system reached more than 81.15%; the above experiments proved that the TiO2 / Fe-g-C3N4 / BC particle electrode prepared by the present invention can achieve efficient degradation of pollutants.
[0070] Comparative Example 1 In this comparative example, the same device as in Example 1 is used, but the prepared TiO2 / Fe-g-C3N4 / BC particle electrode is not added. Two pairs of working electrodes (two anodes and three cathodes) are still used. The cathode is a titanium plate, the anode is a DSA ruthenium iridium electrode, and the power supply is a DC regulated power supply, assembled into a two-dimensional electrocatalytic oxidation system.
[0071] As in Example 1, tetrahydrofuran (THF) was used as the target pollutant, the experimental water was prepared with a COD of 1500 mg / L, the electrolyte was 20 mmol / L Na2SO4, the electrode spacing was 2 cm, and the current density of the electrocatalytic oxidation system was regulated to 20 mA / cm 2 .like Figure 1 As shown, the removal efficiency of tetrahydrofuran (THF) by the two-dimensional electrocatalytic oxidation system reached 77.27%.
[0072] By comparing the treatment effects of Example 1 and Comparative Example 1, it can be seen that the addition of the TiO2 / Fe-g-C3N4 / BC particle electrode significantly improves the degradation of the pollutant THF by the electrocatalytic oxidation system.
[0073] Example 3 The preparation method of the electrolytic cell and particle electrode in this embodiment is consistent with that in Example 1. The cathode is a titanium plate, the anode is a DSA electrode, two pairs of working electrodes are used, a DC regulated power supply is used as the output power supply, and the prepared TiO2 / Fe-g-C3N4 / BC particle electrode is added to assemble into a three-dimensional electrocatalytic oxidation system.
[0074] N,N-dimethylformamide (DMF) was used as the target pollutant. Wastewater with a COD of about 1500 mg / L was prepared. The electrolyte was 20 mmol / L Na2SO4. The dosage of the particle electrode TiO2 / Fe-g-C3N4 / BC was 1 g / L. The electrode spacing was 2 cm. The current density of the electrocatalytic oxidation system was regulated to 20 mA / cm 2 .like Figure 2 As shown, the removal rate of DMF by the three-dimensional electrocatalytic oxidation system reached 37.63%.
[0075] Comparative Example 2 The device in this comparative example is the same as that in Example 3, but the prepared particle electrode is not added, and only a two-dimensional electrocatalytic oxidation system is constructed. The experimental water is the same as that in Example 3, DMF is used as the target pollutant, COD is 1500 mg / L of wastewater, the electrolyte is 20 mmol / L of Na2SO4, the electrode spacing is 2 cm, and the current density of the electrocatalytic oxidation system is regulated to 20 mA / cm 2 .like Figure 2 As shown, after 4 hours of treatment, the COD removal rate of the two-dimensional electrocatalytic oxidation system for wastewater was only 25.13%.
[0076] By comparing the treatment effects of Example 3 and Comparative Example 2, it can be seen that the addition of the TiO2 / Fe-g-C3N4 / BC particle electrode significantly improves the degradation of the pollutant DMF by the electrocatalytic oxidation system.
[0077] Example 4 The preparation method of the particle electrode in this embodiment is consistent with that in Example 1. Two pairs of working electrodes are used, the cathode is a titanium plate, the anode is changed to a BDD electrode, a DC regulated power supply is used as the output power supply, and the prepared TiO2 / Fe-g-C3N4 / BC particle electrode is added to form a three-dimensional electrocatalytic oxidation system.
[0078] The experimental water was wastewater from a chemical plant with a COD of 31750 mg / L. The dosage of the particle electrode TiO2 / Fe-g-C3N4 / BC was 1 g / L, the electrode spacing was 2 cm, and the current density of the electrocatalytic oxidation system was regulated to 50 mA / cm 2 .like Figure 3 As shown, after 4 hours of treatment, the three-dimensional electrocatalytic oxidation system achieved a COD removal rate of 32.54% for wastewater.
[0079] Comparative Example 3 The device in this comparative example is consistent with that in Example 4, the cathode is a titanium plate, the anode is a BDD electrode, but no particle electrode is added, and the chemical plant wastewater (consistent with Example 4) is treated by a two-dimensional electrocatalytic oxidation system, the COD is 31750 mg / L, the electrode spacing is 2 cm, and the current density of the electrocatalytic oxidation system is regulated to 50 mA / cm 2 .like Figure 3 As shown, after 4 hours of treatment, the COD removal rate of the two-dimensional electrocatalytic oxidation system for wastewater was only 22.74%.
[0080] By comparing the treatment effects of Example 4 and Comparative Example 3, it can be seen that the addition of TiO2 / Fe-g-C3N4 / BC particle electrode significantly improves the degradation of COD of this chemical wastewater by the electrocatalytic oxidation system.
[0081] Example 5 The preparation method of the electrolytic cell and particle electrode in this embodiment is consistent with that in Example 4. The cathode is a titanium plate, the anode is a BDD electrode, two pairs of working electrodes are used, a DC regulated power supply is used as the output power supply, and the prepared TiO2 / Fe-g-C3N4 / BC particle electrode is added to assemble into a three-dimensional electrocatalytic oxidation system.
[0082] The experimental water was pharmaceutical wastewater from a pharmaceutical factory with a COD of 27800 mg / L. The dosage of the particle electrode TiO2 / Fe-g-C3N4 / BC was 1 g / L, the electrode spacing was 2 cm, and the current density of the electrocatalytic oxidation system was regulated to 50 mA / cm 2 .like Figure 4 As shown, after 4 hours of treatment, the three-dimensional electrocatalytic oxidation system achieved a COD removal rate of 39.39% for wastewater.
[0083] Comparative Example 4 The device in this comparative example is the same as that in Example 5, but without adding the prepared particle electrode, a two-dimensional electrocatalytic oxidation system is used to treat pharmaceutical wastewater from a pharmaceutical factory with a COD of 27800 mg / L, an electrode spacing of 2 cm, and a current density of 50 mA / cm 2 .like Figure 4 As shown, after 4 hours of treatment, the COD removal rate of the two-dimensional electrocatalytic oxidation system for wastewater was only 28.13%.
[0084] Comparing the treatment effects of Example 5 and Comparative Example 4, it can be seen that the addition of TiO2 / Fe-g-C3N4 / BC particle electrode significantly improves the degradation of COD of this pharmaceutical wastewater by the electrocatalytic oxidation system.
[0085] Example 6 The preparation method of the electrolytic cell and particle electrode in this embodiment is consistent with that in Example 4. The cathode is a titanium plate, the anode is a BDD electrode, two pairs of working electrodes are used, a DC regulated power supply is used as the output power supply, and the prepared TiO2 / Fe-g-C3N4 / BC particle electrode is added to construct a three-dimensional electrocatalytic oxidation system.
[0086] Wastewater from a pesticide factory was treated. The COD was 30700 mg / L, the electrode spacing was 2 cm, and the current density of the electrocatalytic oxidation system was regulated to 50 mA / cm 2 .like Figure 5 As shown, after 4 hours of treatment, the three-dimensional electrocatalytic oxidation system had a COD removal rate of 40.36% for wastewater.
[0087] Comparative Example 5 The device in this comparative example is consistent with that in Example 6. The cathode is a titanium plate, the anode is a BDD electrode, but no particle electrode is added. A two-dimensional electrocatalytic oxidation system is constructed to treat wastewater from a pesticide factory. The COD is 30700 mg / L, the electrode spacing is 2 cm, and the current density of the electrocatalytic oxidation system is regulated to 50 mA / cm 2 .like Figure 5 As shown, after 4 hours of treatment, the removal rate of COD in wastewater by the two-dimensional electrocatalytic oxidation system was only 28.63%.
[0088] By comparing the treatment effects of Example 6 and Comparative Example 5, it can be seen that the addition of TiO2 / Fe-g-C3N4 / BC particle electrode significantly improves the degradation of COD in the pesticide factory wastewater by the electrocatalytic oxidation system.
[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A particle electrode for enhancing electrocatalytic degradation of pollutants in industrial wastewater, characterized in that: The particle electrode is a TiO2 / Fe-g-C3N4 / BC particle electrode, wherein BC is porous biochar, Fe-g-C3N4 is loaded on BC, and TiO2 is loaded on Fe-g-C3N4 / BC.
2. The particle electrode for enhancing electrocatalytic degradation of pollutants in industrial wastewater according to claim 1, characterized in that: The mass of the iron source is 5%-10% of the mass of g-C3N4, the mass of Fe-g-C3N4 is 5%-10% of the mass of BC, and the mass of TiO2 is 10%-15% of the mass of Fe-g-C3N4 / BC.
3. A method for preparing a particle electrode for enhancing electrocatalytic degradation of pollutants in industrial wastewater according to claim 1 or 2, characterized in that: The following steps are involved: Preparation of biochar by pyrolysis of biomass raw materials; Preparation of Fe-g-C3N4 using g-C3N4 and iron source; Fe-g-C3N4 / BC was prepared using biochar and Fe-g-C3N4; TiO2 / Fe-g-C3N4 / BC particle electrode was prepared using Fe-g-C3N4 / BC and TiO2.
4. The method according to claim 3, characterized in that The biomass raw material is wood or straw; The biomass raw materials are crushed and sifted; The moisture content of the biomass raw material is maintained at 15%-20%; The pyrolysis temperature is 400-600°C, the pyrolysis time is 2-6h, and the heating rate is 3-8°C / min; Biochar was pretreated by soaking in acid-base solution.
5. The method according to claim 3, characterized in that: The preparation process of Fe-g-C3N4 using g-C3N4 and an iron source is as follows: g-C3N4 and an iron source are dissolved in water, mixed and stirred, and then separated, washed, and dried to obtain Fe-g-C3N4; Or, the g-C3N4 is prepared by calcining and grinding melamine as a raw material; During stirring, an alcohol solution of sodium borohydride at a concentration of 4-8 mg / mL was also added; The iron source includes ferric nitrate nonahydrate or ferric chloride hexahydrate; The mass of the iron source is 5-10% of the mass of g-C3N4.
6. The method according to claim 3, characterized in that: The preparation process of Fe-g-C3N4 / BC using biochar and Fe-g-C3N4 is as follows: the pretreated biochar and Fe-g-C3N4 are dissolved in water, stirred, dried, and calcined to obtain Fe-g-C3N4 / BC; Or, the stirring time is 6-14h, the drying temperature is 100-110°C, the calcination temperature is 400-500°C, the calcination time is 2-4h, and the heating rate is 2-6°C / min; The mass of Fe-g-C3N4 is 5%-10% of the mass of biochar.
7. The method according to claim 3, characterized in that The preparation process of TiO2 / Fe-g-C3N4 / BC particle electrode prepared by mixing Fe-g-C3N4 / BC and TiO2 is as follows: adding a binder and a dispersant to TiO2 powder to obtain a TiO2 mixture, and then mixing, drying and calcining the Fe-g-C3N4 / BC and TiO2 mixture; The adhesive is 10wt% polytetrafluoroethylene or polyetherketone; The dispersant is anhydrous ethanol; In the TiO2 mixture, the ratio of TiO2, binder and dispersant is 1:(1.5-3):(1.5-3), g / mL / mL; In the preparation process of mixing, drying and calcining the Fe-g-C3N4 / BC and TiO2 mixture, the drying temperature is 80-110°C, the drying time is 0.5-2h, the calcination temperature is 300-500°C, the heating rate is 2-6°C / min, and the calcination time is 4-5h; The mass of TiO2 is 10%-15% of the mass of Fe-g-C3N4 / BC.
8. Use of the particle electrode for enhancing the electrocatalytic degradation of pollutants in industrial wastewater according to claim 1 or 2 in enhancing the electrocatalytic degradation of pollutants in industrial wastewater.
9. The use according to claim 8, characterized in that: The industrial wastewater includes wastewater containing tetrahydrofuran and / or N,N-dimethylformamide, chemical wastewater, pharmaceutical wastewater or pesticide wastewater.
10. A method for enhancing electrocatalytic degradation of pollutants in industrial wastewater, characterized in that: The steps include: (1) constructing a three-dimensional electrocatalytic oxidation system in an electrolytic cell, wherein the system comprises an anode, a cathode, an electrolyte solution and a particle electrode suspended in the electrolyte solution; the particle electrode is as described in claim 1 or 2; (2) mixing industrial wastewater with the electrolyte solution; (3) applying voltage to the three-dimensional electrocatalytic oxidation system to electrocatalytically oxidize the industrial wastewater.
Citation Information
Patent Citations
Granule electrode possessing photoelectric catalytic function and its uses
CN101187646A
Method for degrading nitrobenzene waste water by polyphase electrocatalytic oxidation-Fenton coupling process and reactor thereof
CN101838074A
Particle electrode for photocatalytic three-dimensional electrode / electro-Fenton system and preparation method thereof
CN103739043A
Preparation method of composite electrode of carbon nitride / titanium dioxide nanotube
CN103771565A
Iron-nitrogen-doped titanium dioxide-loaded carbon fiber composite photocatalyst and preparation method thereof
CN105597805A
Cited By
BDD composite electrode, electrode preparation method and medical wastewater treatment equipment
CN120757202A
